Предмет: Алгебра, автор: lostll

раскрой скобки и упростит выражения. 1)t² (3t-5)+4t(t²-t)= 2)-4b²(t²-b²)+3b²(b²-t²) =

Ответы

Автор ответа: tihontihon262
0

Ответ:

1)  7t^3-9t^2

2)  7b^4-7t^2b^2

Объяснение:

1) t^2(3t-5)+4t(t^2-t)=

(3t*t^2-5*t^2)+(t^2*4t-t*4t)=

(3t^3-5t^2)+(4t^3-4t^2)=

3t^3-5t^2+4t^3-4t^2=

7t^3-9t^2

2) -4b^2(t^2-b^2)+3b^2(b^2-t^2)=

3b^2(b^2-t^2)-4b^2(t^2-b^2)=

(b^2*3b^2-t^2*3b^2)-(t^2*4b^2-b^2*4b^2)=

(3b^4-3t^2b^2)-(4t^2b^2-4b^4)=

3b^4-3t^2b^2-4t^2b^2+4b^4=

7b^4-7t^2b^2=

7b^2(b^2-t^2)=

7b^2(b-t)(b+t)

Похожие вопросы